2018
DOI: 10.1021/acs.macromol.8b00239
|View full text |Cite
|
Sign up to set email alerts
|

Liquids That Freeze When Mixed: Cocrystallization and Liquid–Liquid Equilibrium in Polyoxacyclobutane–Water Mixtures

Abstract: We show that liquid polyoxacyclobutane −[CH2–CH2–CH2–O] n – when mixed with water at room temperature precipitates solid cocrystals of the polymer and water. Cocrystals can also be formed by simply exposing the liquid polymer to saturated humidity. This appears to be the only known example of nonreacting liquids combining to form a solid cocrystal, also known as a clatherate, at room temperature. At high temperatures, the same polymer–water mixtures phase separate into two coexisting liquid phases. This combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…To the authors' knowledge, only one solid cocrystal system comprised of nonreacting liquids has been previously reported; however, this system consisted of oligomeric polyoxacyclobutane (POCB) and water. 43 Standing in stark contrast to 18 and 19, the melting point of a cocrystal of 2480 g/mol POCB and water is 39 °C, only 19 °C above the normal melting point for the pure POCB. The lowest molecular weight POCB to exhibit cocrystal formation was 300 g/mol, still much higher than the molecular weights of either dicyclohexylamine (181 g/mol) or 2-methylpiperdine (99 g/mol).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To the authors' knowledge, only one solid cocrystal system comprised of nonreacting liquids has been previously reported; however, this system consisted of oligomeric polyoxacyclobutane (POCB) and water. 43 Standing in stark contrast to 18 and 19, the melting point of a cocrystal of 2480 g/mol POCB and water is 39 °C, only 19 °C above the normal melting point for the pure POCB. The lowest molecular weight POCB to exhibit cocrystal formation was 300 g/mol, still much higher than the molecular weights of either dicyclohexylamine (181 g/mol) or 2-methylpiperdine (99 g/mol).…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…To the authors’ knowledge, only one solid cocrystal system comprised of nonreacting liquids has been previously reported; however, this system consisted of oligomeric polyoxacyclobutane (POCB) and water . Standing in stark contrast to 18 and 19 , the melting point of a cocrystal of 2480 g/mol POCB and water is 39 °C, only 19 °C above the normal melting point for the pure POCB.…”
Section: Resultsmentioning
confidence: 99%
“…The typical coal chemical wastewater is rich in Na 2 SO 4 and NaCl, so it can be considered as a comparatively simple water–salt system. Recently, the multistage separation method of Na 2 SO 4 and NaCl based on the phase equilibria of the Na + //Cl – , SO 4 2– –H 2 O system in pure water has been reported. , However, the existence of organic impurities in wastewater, which is unable to be eliminated, will influence the crystallization process and the quality of subsequent salts. Su et al studied the effect of phenol on the crystallization of Na 2 SO 4 . They found that the existence of phenol could suppress the solubility of Na 2 SO 4 in water.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the multistage separation method of Na 2 SO 4 and NaCl based on the phase equilibria of the Na + // Cl − , SO 4 2− −H 2 O system in pure water has been reported. 11,12 However, the existence of organic impurities in wastewater, which is unable to be eliminated, will influence the crystallization process and the quality of subsequent salts. 13 Su et al 16 studied the effect of phenol on the crystallization of Na 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…These devices perform well when compared to other carbon nanotube-based field-effect transistor memory devices (Table S1). POCB displays very interesting phase behavior 32 and crystallizes with water at room temperature to form structures with hydrogen-bonded 1-D chains of water molecules propagating through the structure. We believe that this structure allows for trapping and shuttling of charge under applied gate bias by proton migration in the oligomer hydrate crystals which is the cause of the large observed hysteresis in s-SWCNT-FET measurements.…”
mentioning
confidence: 99%